Hepatic Steatosis: Can herbs cure this? - Rehan, Rabia; Perveen, Khalida; Imtiaz, Fauzia; Mubeen, Sahar (International Journal of Endorsing Health Science Research, 2018)
Background: Accumulation of fat in the liver is known as liver steatosis which occurs as a result of obesity. Ginsenoside is glycosylated saponins easily found in Asia, Egypt and China. The aim of this study is to determine the role ginseng in treating fatty changes of liver measured by weight, size, and enzymes. Methodology: It was an experimental study on animals. Ginseng root extract was prepared under expert supervision. Fifty male rats were divided into five groups each has to contain ten animals. Group 1 on balanced diet (control), Group 2 on high fat diet (HFD) obese control, Group 3 on HFD + Ginsenoside (100mg/kg body weight), Group 4 on HFD + Ginsenoside (200mg/kg body weight) and Group 5 on HFD + Ginsenoside (400mg/kg body weight). Animals were weighted at commencement then weekly and finally before sacrifice. Animals were sacrificed under chloroform anesthesia, the liver was isolated and removed. Liver weight and size were measured. Blood was collected through cardiac puncture and sent to DDRRL for LFT. Results: By giving HFD, increase in liver weight, as well as the liver size and liver enzymes, was observed. Ginsenoside when given to HFD induced liver steatosis leads to decrease in liver weight, liver size, and liver enzymes. It had a prompt effect on reducing body weight as well as liver weight by reducing fat contents of the body. Conclusion: The study provides evidence that Ginsenoside has hepatoprotective effects by reducing the weight, size, and enzymes of the liver.